No Place to Go: Internally Displaced Persons in Burma
Produced in collaboration with WITNESS partner Burma Issues, NO PLACE TO GO is based upon the harrowing testimony of internally displaced persons (IDPs) in eastern Burma and the video documentation of their plight. The IDPs tell the story of their experiences as the Burmese military government has systematically killed its own people using forced labor, forced movement, arbitrary executions and massacres. Almost a million people, primarily ethnic minorities such as the Karen, have been driven from their homes and forced to run into relocation camps or into the jungle, where they have limited access to healthcare, shelter, food or education, and must constantly relocate to avoid attack or capture by the Burmese forces. Many are subsequently forced to flee as refugees into neighboring Thailand.